Anomalous Dielectric Behavior in Co-Doped TiO2 Nanotubes: Effect of Oxygen Vacancy Mediated Defect Dipole Pairs. (22nd November 2021) - Vijayan P, Pournami; Vijayan P, Poornima; Chandran, Anoop; George, K. C.
Abstract : Titanium dioxide (TiO2 ) nanotubes are considered to be unique in terms of their physical properties and high dielectric constant. The oxygen vacancies in TiO2 play a crucial role in the dielectric behavior, which can be tuned by doping with proper materials. Herein, the changes in the dielectric behavior, as well as defect concentration of TiO2 nanotubes by Cobalt (Co) doping, have been evaluated. For this purpose, Co-doped TiO2 nanotubes have been synthesized by using combined sol-gel and hydrothermal methods. By analyzing photoluminescence spectra, the intensities and positions of five emission peaks are clearly assigned. The PL peaks could be sensibly explained by various mechanisms, such as direct allowed transition, oxygen vacancies, and self-trapped excitons. The dielectric behavior of Co-doped TiO2 nanotubes with controlled oxygen vacancies is explained. The dielectric constant is particularly at its highest in higher Co-doped TiO2 nanotubes. The current investigation provides new insight into the mechanisms underlying the anomalous dielectric properties shown by Co-doped TiO2 nanotubes, as evident from the movement of oxygen vacancies. It demonstrates the influence of defect dipoles, 2CoTi —Vo ̇, in the anomalous dielectric behavior observed for Co-doped TiO2 nanotubes.